2021
DOI: 10.3389/fpubh.2021.673451
|View full text |Cite
|
Sign up to set email alerts
|

Educational Attainment Decreases the Risk of COVID-19 Severity in the European Population: A Two-Sample Mendelian Randomization Study

Abstract: Observational studies have reported that the severity of COVID-19 depends not only on physical conditions but also on socioeconomic status, including educational level. Because educational attainment (EA), which measures the number of years of schooling, is moderately heritable, we investigated the causal association of EA on the risk of COVID-19 severity using the Mendelian randomization (MR) approach. A two-sample MR analysis was performed using publicly available summary-level data sets of genome-wide assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 42 publications
7
31
1
Order By: Relevance
“…Physicians are at a significant increased risk too compared to non-HCWs, but the risk is lower compared to nurses, in line with the results reported by Poletti et al [12], while another recent report did not find significantly increased risks according to the job role of the HCW [35]. The different risks for doctors can be possibly explained by the differences in the type of close contacts with the patients and in the duration of the contact in the examined sample; a possible role of a higher education level and training, influencing the appropriate use of the PPE [37], cannot be excluded. Interestingly, in the category of "other HCW", including a heterogeneous group of health personnel such as obstetrics, physiotherapists and various others, the odds of having COVID-19 were not significantly increased compared to non-HCW.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Physicians are at a significant increased risk too compared to non-HCWs, but the risk is lower compared to nurses, in line with the results reported by Poletti et al [12], while another recent report did not find significantly increased risks according to the job role of the HCW [35]. The different risks for doctors can be possibly explained by the differences in the type of close contacts with the patients and in the duration of the contact in the examined sample; a possible role of a higher education level and training, influencing the appropriate use of the PPE [37], cannot be excluded. Interestingly, in the category of "other HCW", including a heterogeneous group of health personnel such as obstetrics, physiotherapists and various others, the odds of having COVID-19 were not significantly increased compared to non-HCW.…”
Section: Discussionsupporting
confidence: 82%
“…The results of our study confirm that frontline HCW dealing with COVID-19 patients are at a significantly increased risk when compared to non-HCW: the risk is higher in nurses and nurse aides and other HCW having direct contact with patients [9][10][11][12][13][14][34][35][36][37]. Physicians are at a significant increased risk too compared to non-HCWs, but the risk is lower compared to nurses, in line with the results reported by Poletti et al [12], while another recent report did not find significantly increased risks according to the job role of the HCW [35].…”
Section: Discussionsupporting
confidence: 76%
“…Besides, we found that the coefficient of educational attainment turned positive. This finding is against with a claim that educational attainment decreases the risk of COVID-19 severity (Yoshikawa & Asaba, 2021 ).…”
Section: Resultsmentioning
confidence: 61%
“…Thus, the magnitude of association derived from previous observational studies and this MR study cannot be directly compared. It also came to our attention that Yoshikawa et al published a univariable MR analysis very recently by making use of a smaller number of 235 genetic instruments for education attainment [ 27 ] extracted from the latest meta-analysis but a reduced data set comprising 766,345 individuals after excluding the 23andMe samples. In contrast, our current study had higher statistical power due to the use of more than 1110 independent SNPs derived from the same but complete data set consisting of 1,131,881 individuals as genetic instruments [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our current study had higher statistical power due to the use of more than 1110 independent SNPs derived from the same but complete data set consisting of 1,131,881 individuals as genetic instruments [ 16 ]. In addition, they did not conduct multivariable MR analyses to uncover the potential mechanisms, and they did not examine the causal effects of education attainment on SARS-CoV-2 infection and COVID-19 hospitalization [ 27 ]. Likewise, the causal association of intelligence with COVID-19 outcomes was not examined in the study conducted by Yoshikawa et al…”
Section: Discussionmentioning
confidence: 99%